Die Authentizität in Maja Haderlaps Roman Engel des Vergessens - Glišič, Miša (Vestnik za tuje jezike, 2014)
This article analyses the authenticity of memories in the second half of the 20th century in Carinthia. The segmentation of historical authenticity is visible in the historical reminiscence of traumatic historical events in relation to social interaction. The combination of social, political und cultural elements affects the divergent experience of individuals in determinated environment. The complexity of the novel is seen in the inner feelings, which characterization relates to emotions and the subconscious of the population. The article focuses on the female perspective as well as on the role of women in the story. The author proves with her experience of unconsciously the unsolved problematic of her own literalizing of history. The personality of the writer is shown in the examples of double literary, personal and lingual identity.
Keywords: Haderlap, Maja, 1961-; Haderlap, Maja: Engel des Vergessens; avstrijska književnost; Slovene literature; slovenska književnost; prose; proza; literarizacija zgodovine; avstrijska Koroška; Carinthia; vloga ženske; ženski liki; večkulturnost; iskanje identitete; manjšinsko vprašanje